Corrosion Monitoring using Radio Frequency Identification - Nur Melatee binti Mohd Fauzi, Nur Melatee (Universiti Teknologi Petronas, 2010)
For the purpose of this project, the RFID tag had been wrapped with aluminium foil and immersed in 0.5% Sodium Hydroxide solution to create corrosive condition to the aluminium. The signal strength readings and weight loss of corroded metal were recorded for every 15 minutes until the aluminium foil was totally dissolved. From the weight loss, the corrosion rate was calculated and the thickness of metal corrodes was compared with the signal strength obtained from the RFID software.